A Study on the Influence of 5G on Intelligent Automation and Industrial Digitization (International Journal of Food and Nutritional Sciences, 2022)
The new Fifth generation (5G) wireless technology is providing us with more efficiency and the ability to move at lightning speed. Though 4G is already active, future traffic in this band is expected to expand steadily along with the number of users and devices that can access it. Recent years have seen the introduction of some research activities and initiatives involving major mobile infrastructure manufacturers, academic institutions, and international mobile network operators, all working to lay the groundwork for 5G mobile communication technologies. Still, not much is known about the structure or capabilities of 5G mobile services when they become available. This study examines the development and evolution of mobile wireless technology, this study shows the significance of 5G revolutionary networks by discussing its main enabling technologies, trends, difficulties, applications in various manufacturing sectors, and contribution to the future of infinite connection, intelligent automation, and industrial digitalization.